2011
DOI: 10.1258/jtt.2011.110707
|View full text |Cite
|
Sign up to set email alerts
|

Use of telephone and SMS reminders to improve attendance at hospital appointments: a systematic review

Abstract: Patients failing to attend hospital appointments contribute to inefficient use of resources. We conducted a systematic review of studies providing a reminder to patients by phone, short message service (SMS) or automated phone calls. A PubMed search was conducted to identify articles published after 1999, describing studies of non-attendance at hospital appointments. In addition, we searched the references in the included papers. In total, 29 studies were included in the review. Four had two intervention arms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
178
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(198 citation statements)
references
References 30 publications
9
178
2
6
Order By: Relevance
“…Second, only one third of the potentially eligible sample participated in the study and we were not able to assess socio‐economic differences between participants and non‐participants, which may restrict the study's generalizability. Not unlike tendencies among people with chronic conditions in general 29, the frequency of non‐participation was considerable in the present study population, which is a possible threat to the study's validity. In addition, two out of three participants were female, and women generally report higher levels of diabetes‐related distress than men 30.…”
Section: Discussionmentioning
confidence: 71%
“…Second, only one third of the potentially eligible sample participated in the study and we were not able to assess socio‐economic differences between participants and non‐participants, which may restrict the study's generalizability. Not unlike tendencies among people with chronic conditions in general 29, the frequency of non‐participation was considerable in the present study population, which is a possible threat to the study's validity. In addition, two out of three participants were female, and women generally report higher levels of diabetes‐related distress than men 30.…”
Section: Discussionmentioning
confidence: 71%
“…Eleven SRs met the inclusion criteria for review 2 (Table 1). [16][17][18][34][35][36][37][38][39][40][41] These SRs either examined a single technology, eg, an SR of short message service (SMS) reminder systems, 17 or explored the role of information technologies along a patient care pathway, one of which might be appointment reminder systems. 41 The quality of included reviews was variable ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…17,35,39,41 Two reviews did not pass the minimum standard for SRs. 37,38 Of the 31 RCTs that met our inclusion criteria for review 2,4, only ten were uniquely identified by our review. The included RCTs related to the use of systems to remind patients to attend a health-related appointment that had already been scheduled ( Abbreviations: PRiSMA, Preferred Reporting items for Systematic Reviews and Meta-Analyses; SRs, systematic reviews; RCTs, randomized controlled trials; Ti, titles; AB, abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…7,[43][44][45][46][47][48] We decided to include in our review only RCTs, systematic reviews, and meta-analyses of RCTs, and not intervention trials using less rigorous methods, such as quasi-experimental studies or reviews containing nonrandomized studies, because RCTs provide stronger and more unbiased estimations of the impact of interventions. This restriction clearly limited the number of articles eligible for this review as our search criteria returned only nine RCTs with 4,604 participants from developing countries.…”
Section: Discussionmentioning
confidence: 99%